Biological changes in the pregnancy‐postpartum period and subsequent cardiometabolic risk—UPSIDE MOMS: A research protocol. Issue 4 (16th May 2021) - Groth, Susan W.; Fernandez, I. Diana; Block, Robert C.; Thurston, Sally W.; Wong, Eunyoung; Brunner, Jessica; Mayo, Nicole; Kapula, Ntemena; Yu, Yang; Meng, Ying; Yeh, Kuan‐Lin; Kinkade, Carolyn W.; et al.
Abstract: Multiple physiological changes occur in pregnancy as a woman's body adapts to support the growing fetus. These pregnancy‐induced changes are essential for fetal growth, but the extent to which they reverse after pregnancy remains in question. For some women, physiological changes persist after pregnancy and may increase long‐term cardiometabolic disease risk. The National Institutes of Health‐funded study described in this protocol addresses a scientific gap by characterizing weight and biological changes during pregnancy and an extended postpartum period in relation to cardiometabolic risk. We use a longitudinal repeated measures design to prospectively examine maternal health from early pregnancy until 3 years postpartum. The aims are: (1) identify maternal weight profiles in the pregnancy‐postpartum period that predict adverse cardiometabolic risk profiles three years postpartum; (2) describe immune, endocrine, and metabolic biomarker profiles in the pregnancy‐postpartum period, and determine their associations with cardiometabolic risk; and (3) determine how modifiable postpartum health behaviors (diet, physical activity, breastfeeding, sleep, stress) (a) predict weight and cardiometabolic risk in the postpartum period; and (b) moderate associations between postpartum weight retention and downstream cardiometabolic risk. The proposed sample is 250 women. This study of mothers is conducted in conjunction with the Understanding Pregnancy Signals and Infant Development study, which examines child health outcomes. Biological and behavioral data are collected in each trimester and at 6, 12, 24, and 36 months postpartum. Findings will inform targeted health strategies that promote health and reduce cardiometabolic risk in childbearing women.